Environmental perception of residents of the municipality Farias Brito, CE, on pollution Carius river - Pereira, Pedro Silvino; Pereira, Andréia Matos Brito; Castro, Cícero Luciano Ferreira de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
Most towns facing major problems such as river pollution, poor sanitation, among others. Today has sought an improvement in quality of life and environment. The environmental quality in turn relates to the improvement of livelihood, community arouse becoming important for an environmental awareness toward the conservation of the environment in which they live. This research was conducted with the people living around the Rio Cariús. The objective was to investigate the perception of people living around the river Cariús over the same. For the study we used a qualitative approach with quantitative elements, and employed a semi-structured questionnaire, which were approached at random, a hundred local residents. Data were tabulated in Excel. According to the survey 53% were female; 17% knew what they were environmental education; 58% said that the environment is defined as nature and yet replied that the way to improve the lives of the river would be the city have a sewerage system (27%) and be developed in an environmental education program to minimize environmental impacts and how to raise awareness.